Potential of Colicin as an Antibacterial Agent in Escherichia coli - Cynthia Gozali; Andriansjah Rukmana (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
The development of antibiotics calls for the critical consideration of instances of resistance. Infectious disorders brought on by resistant bacterial infections could affect the entire world. It is believed that the protein that the bacteria generate may one day replace antibiotics as an alternative antibacterial agent. Both Gram-positive and Gram-negative bacteria have the ability to manufacture bacteriocin. The bacteriocin type produced by Escherichia coli, notably colicin, has been demonstrated to inhibit the same bacteria through various essential methods. Colicin, a substance made by an E. coli cell, is also capable of protecting itself from attack; however, this defense mechanism has not yet been identified. The traits of colicin and the method by which it functions as a different antimicrobial agent to inhibit other bacteria will be covered in this article. We analyze the potential of colicin as an antibacterial agent in E. coli using PRISMA methods from diverse academic sources. Here, we found that the structure of the colicin, namely its central receptor domain, aids in the recognition of target cells. Promising results were found in recent studies on the antibacterial effects of the E. coli and colicin combination